2001
DOI: 10.1108/10222529200100003
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the new IIA Standards and the internal auditing profession

Abstract: The Institute of Internal Auditors is in the process of developing new standards for the internal auditing profession. The first set of these standards will be implemented with effect from 1 January 2002. The purpose of professional standards is to lay down the minimum requirements to be maintained for acceptable practice. In June 1999, a new formal definition of internal auditing was adopted to address relevant issues with which internal auditing is currently faced. Existing standards, when read in conjunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In South Africa, Coetzee and du Bruyn (2001) investigated the limitations of the previous Standards and compared them to the changes in the new IIA Standards. They concluded that the changes to the Standards successfully address the challenges faced by the internal audit profession in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In South Africa, Coetzee and du Bruyn (2001) investigated the limitations of the previous Standards and compared them to the changes in the new IIA Standards. They concluded that the changes to the Standards successfully address the challenges faced by the internal audit profession in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 1947, the IIA focused the IAF's role on checking accounting records, detecting financial irregularities, and assisting external auditors (Swinkels, 2012;Moeller, 2009). In a further evolution, the internal audit profession is required to articulate modern developments (Coetzee and Bruyn, 2001;Hass et al, 2006), so that since 1999 until now IAF has been defined as "an independent, objective assurance and consulting activity designed to add value. and improve an organization's operations.…”
Section: The Role Of the Internal Audit Functionmentioning
confidence: 99%
“…and improve an organization's operations. It helps an organization accomplish its objectives by bringing a systematic, disciplined approach to evaluate and improve the effectiveness of risk management, control and governance processes (Coetzee and Bruyn, 2001;Pickett, 2010).…”
Section: The Role Of the Internal Audit Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global corporate scandals and breakdowns in the financial services sector have also increased the role of internal audit in providing assurance and consulting services on risk management, governance and internal control. This progress and awareness also brought with it a renewed focus not only on the technical skills but also on the soft skills required of those practising as internal auditors (Barac et al , 2013; Plant et al , 2013; IIARF, 2016; Steyn et al , 2013; Coetzee et al , 2014; Cowan et al , 2013; Jackson, 2020). Gopinath (in Piper, 2020), chief economist at the International Monetary Fund, stated in an interview that “[t]his [the COVID-19 pandemic] is much stronger than the global financial crisis” which means that the role of internal audit, in reinforcing risk management, governance and internal control, will be more important than ever before during and post the COVID-19 crisis (Piper, 2020; Wright, 2020).…”
Section: Introductionmentioning
confidence: 99%